(:unas) unassigned - Mettas, Christodoulos (My University, 2018)
Project Title: Vasilikos Power Plant Project, Phase 3 (Unit No. 4) Assigned duties: 1. Assistant Surveyor 2. Earthworks 3. Measurements for valuation purposes 4. Project Safety 5. Supervision of the project 6. Assisting in the laboratory Planning and executing a range of activities for road works, such as excavations, laying of various utilities and laying of asphalt mixtures.